Delusional altruism : why philanthropists fail to achieve change and what they can do to transform giving - Putnam-Walkerly, Kris (Wiley, 2020)
"The U.S. economy is positioned for tremendous growth, and $30 trillion dollars in assets will be transferred to the next generation among ultra-high net worth families during the next three decades. Current philanthropic assets will commensurately grow, and there is enormous opportunity to capitalize on this wealth transfer to increase philanthropic giving. But how will philanthropists spend this money for social good? While there are numerous shining examples of positive social change spurred by philanthropy, most current philanthropic practices are hamstrung by bureaucracy, sloth, underperformance, and a lack of creativity. Without a serious overhaul of philanthropic practice, donors, foundations, and corporate giving will under-leverage the coming philanthropy boom. Delusional Altruism provides practical advice and guidance for philanthropists who want to avoid traditional pitfalls in giving and become more effective at delivering social change"--